Agent-based model experiments cast doubt on Dunnell's adaptive waste explanation for cultural elaboration. Issue 1 (1st January 2019) - Carleton, W. Christopher; McCauley, Brea; Costopoulos, André; Collard, Mark
ABSTRACT: Ancient monuments are puzzling from an evolutionary perspective. It is obvious that their construction would have been costly in terms of energy, but it is not clear how they would have enhanced reproductive success. In the late 1980s, Robert Dunnell proposed a solution to this conundrum. He argued that wasting energy on monuments and other forms of what he called "cultural elaboration" was adaptive in highly variable environments. Here, we report a study in which we used an agent-based model to test Dunnell's hypothesis. We found that the propensity to waste was subject to strong negative selection regardless of the level of environmental variability. At the start of the simulation runs, agents wasted ca. 50% of the time but selection rapidly drove that rate down, ultimately settling at ca. 5–7%. This casts doubt on the ability of Dunnell's hypothesis to explain instances of cultural elaboration in the archaeological record.